Fixed Point Theorems of \(L\)-Fuzzy Mappings Via a Rational Inequality - Shahzad, Aqeel; Shoaib, Abdullah; Mahmood, Qasim (Communications in Mathematics and Applications, 2018)
In this paper some fixed point results for \(L\)-fuzzy mappings via a rational inequality are obtained. An example is also given which supports the proved result.